EFEKTIFITAS PENDIDIKANKEWIRAUSAHAANDAN SELF EFFICACY TERHADAP MINAT BERWIRAUSAHA MAHASISWA FEBI IAIN LANGSA - fasya fasya (IAIN Langsa, 2017)
This study attempts to know the influence of direct and indirect entrepreneurship education variable, self-efficacy toward entrepreneurship intention. The population of this research was all students FEBI IAIN Langsa who has taken course lecture entrepreneurship. Sample taken to technique non-probability sampling kind of purposive sampling, and the sample of the 60 student who active. Research methodology using methods survey with a quantitative approach. Analysis of data using analysis path by program assistance MSI, SPSS version 16 and LISREL 8,8 (student). The results of the first structural equation showed that education variable entrepreneurship affect self-efficacy of 96 % with t value (39,05) > t table (1,67). The second structural equation test results showed that self-efficacy variables did not influence the entrepreneurship intention where t value < t table. However, entrepreneurship education, self-efficacy in partial affect entrepreneurial intentions by 72% with t value (2,94) > t table (1.67). The results of data analysis show entrepreneurship education to students Langsa FEBI IAIN positively influence the entrepreneur intentions with t value (39.05) > t table (1.67), then (H1 accepted). Self-efficacy variables negatively does not affect entrepreneur intentions with the value of the t (-0.58) < t table (1.67), then (H2 rejected). The entrepreneurship education variable positively influence self-efficacy with t value (2.94) > t table (1.67), then (H3 accepted). The research recommended the need for an encouragement intentions of students, faculty are expected to provide self-efficacy students to never give up in entrepreneurship, and provide concrete examples of successful entrepreneurs.